INTEGRATING COLLABORATIVE SKILLS IN 8TH GRADE ENGLISH TEACHING LESSON PLANS AT JUNIOR HIGH SCHOOL - Ghyarlina Triyani; Darmahusni Darmahusni (Universitas Islam Sumatera Utara (UISU), 2021)
Collaboration is one of the 21st-century skills needed to survive in this era. The need in society to think and work together on issues of critical concern has increased, shifting the emphasis from individual efforts to group work, from independence to community. Integrating Collaborative skills in the educational field, particularly in assessment, has been broadly employed. However, lesson plans that incorporate collaborative skills are lacking. This study aims to explore the collaborative skill in English teaching lesson plan in junior high school in Indonesia. A content analysis approach is used in this study. The data was analyzed using a systematic content descriptive text methodology based on the ACER (Australian Council for Educational Research) Framework, which was used in this study as an instrument to analyze lesson plans to see if they were integrating or not. The expected result of the study is that Collaborative skills are found in lesson plans, indicators, and the learning process.